2020
DOI: 10.3390/en13133449
|View full text |Cite
|
Sign up to set email alerts
|

Critical Review of Mitigation Solutions for SSO in Modern Transmission Grids

Abstract: The replacement of conventional generation by power electronics-based generation changes the dynamic characteristics of the power system. This results in, among other things, the increased susceptibility to subsynchronous oscillations (SSO). First, this paper discusses three recently emerging SSO phenomena, which arise due to the interactions between (1) a doubly-fed induction generator and a series compensated transmission system; (2) a voltage source converter (VSC) and a weak grid; and (3) nearby VS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 77 publications
0
21
0
Order By: Relevance
“…Solutions for mitigating DFIG-SSR can be based on (i) modifications in existing control algorithms of the DFIG (i.e., control solutions), (ii) installation of new hardware equipment or modification of existing hardware equipment (i.e., hardware solutions), and (iii) coordination between the power system state and existing or new controls (i.e., system level coordination) [1]. Control solutions are implemented in the power electronics interfaced device under consideration (in this case, the DFIG).…”
Section: Overview Of Hardware Solutions For Mitigating Dfig-ssrmentioning
confidence: 99%
See 3 more Smart Citations
“…Solutions for mitigating DFIG-SSR can be based on (i) modifications in existing control algorithms of the DFIG (i.e., control solutions), (ii) installation of new hardware equipment or modification of existing hardware equipment (i.e., hardware solutions), and (iii) coordination between the power system state and existing or new controls (i.e., system level coordination) [1]. Control solutions are implemented in the power electronics interfaced device under consideration (in this case, the DFIG).…”
Section: Overview Of Hardware Solutions For Mitigating Dfig-ssrmentioning
confidence: 99%
“…On the other hand, when the goal is to mitigate DFIG-SSR by means of any other FACTS device, it will have to be equipped with a supplementary damping controller (SDC). Several of such cases are reported in Reference [1]. Installing a FACTS device (except for TCSC) for mitigating DFIG-SSR is only cost-effective when additional power system support, such as voltage control, is required.…”
Section: Overview Of Hardware Solutions For Mitigating Dfig-ssrmentioning
confidence: 99%
See 2 more Smart Citations
“…Some previous studies such as [9,10] have shown that the synchronization system parameters affect the power system stability in the case of weak grids. Besides the impact of the Power System Stabilizer (PSS) on the SSR damping has been previously demonstrated in [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%